2020
DOI: 10.1038/s41598-020-71117-4
|View full text |Cite
|
Sign up to set email alerts
|

Host age is not a consistent predictor of microbial diversity in the coral Porites lutea

Abstract: Corals harbour diverse microbial communities that can change in composition as the host grows in age and size. Larger and older colonies have been shown to host a higher diversity of microbial taxa and this has been suggested to be a consequence of their more numerous, complex and varied micro-niches available. However, the effects of host age on community structure and diversity of microbial associates remain equivocal in the few studies performed to date. To test this relationship more robustly, we use estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(87 reference statements)
2
7
0
Order By: Relevance
“…Our analysis shows a differentiation in the microbial communities associated with the structures sampled, with the holdfast harboring the most distinct community. This is in line with studies performed on other marine organisms from the region, which have shown microbial community divergence over small spatial scales in seagrasses, mangroves and corals [32][33][34]; the same S. ilicifolium structures have also been shown to harbor distinct fungal communities in Singapore [39]. Like other studies examining algal associated microbiota, we show that holdfasts and leaves contain a large proportion of Alphaproteobacteria and Gammaproteobacteria; however, noticeable by their absence in both of these structures, samples collected in Singapore do not contain the class Flavobacteria in comparison to those collected from temperate environments [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis shows a differentiation in the microbial communities associated with the structures sampled, with the holdfast harboring the most distinct community. This is in line with studies performed on other marine organisms from the region, which have shown microbial community divergence over small spatial scales in seagrasses, mangroves and corals [32][33][34]; the same S. ilicifolium structures have also been shown to harbor distinct fungal communities in Singapore [39]. Like other studies examining algal associated microbiota, we show that holdfasts and leaves contain a large proportion of Alphaproteobacteria and Gammaproteobacteria; however, noticeable by their absence in both of these structures, samples collected in Singapore do not contain the class Flavobacteria in comparison to those collected from temperate environments [6].…”
Section: Discussionsupporting
confidence: 91%
“…Research examining the macrophyte-associated microbiome shows that microbial communities associated with different tissues or plant structures contain different communities, likely a consequence of the different roles different parts play in promoting host survival [ 29 , 30 ]. These communities can also be significantly different even over relatively small spatial scales, such as less than 10 km in some cases [ 31 , 32 , 33 , 34 ]. Photophysiological and biochemical heterogeneity between structures has been documented for Sargassum spp., with differences in photosynthetic rates [ 35 ], phlorotannin content [ 36 ] and C:N ratios [ 37 ] being reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, work is now challenging the notion that variance is low in microbial communities, and congruent with other research examining marine microbiomes (Cúcio et al, 2016;Crump et al, 2018;Bay et al, 2020;Osman et al, 2020;Tan et al, 2020;Wainwright et al, 2020) we show that bacterial communities can be significantly different between sampling location and structure examined, and this spatial variance is particularly strong in sediment samples in comparison to living seagrass structures. This is consistent with previously proposed hypotheses suggesting that habitats offered by living plant organs (i.e., leaf, fruit, etc.)…”
Section: Discussionsupporting
confidence: 85%
“…As climate change progresses and coastal habitats are further degraded by land use changes, eutrophication, and other anthropogenic activities, many of these coastal ecosystems are predicted to become net sources of carbon instead of sinks as microbial communities change in response and sequestered carbon becomes available for microbial cycling [17,[19][20][21][22][23][24]. Consequently, mangroves and other coastal habitats, along with their associated blue carbon stocks, are unlikely to fulfil their claimed potential as nature based climate solutions, and many of their benefits are likely overstated [15,[25][26][27][28] The importance of the microbiome in maintaining and promoting host health has been recognised in many organisms in both terrestrial and marine environments [29][30][31][32][33], and the role of the microbiome in promoting plant growth and resilience in terrestrial plants is well established [34,35]. However, the ecological importance of the coastal microbiome is not yet well-understood, although several studies have shown that fungal and bacterial diversity are key to habitat restoration in marine environments [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the microbiome in maintaining and promoting host health has been recognised in many organisms in both terrestrial and marine environments [2933], and the role of the microbiome in promoting plant growth and resilience in terrestrial plants is well established [34, 35]. However, the ecological importance of the coastal microbiome is not yet well-understood, although several studies have shown that fungal and bacterial diversity are key to habitat restoration in marine environments [5, 8].…”
Section: Introductionmentioning
confidence: 99%